2015
DOI: 10.1186/s12888-015-0661-0
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-education for substance use and antisocial personality disorder: a randomized trial

Abstract: BackgroundAntisocial personality disorder often co-exists with drug and alcohol use disorders.MethodsThis trial examined the effectiveness of offering psycho-education for antisocial personality disorder in community substance use disorder treatment centers in Denmark. A total of 176 patients were randomly allocated to treatment as usual (TAU, n = 80) or TAU plus a psycho-educative program, Impulsive Lifestyle Counselling (ILC, n = 96) delivered by site clinicians (n = 39). Using follow-up interviews 3 and 9 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…Our study was not powered to test such an association a priori, as the power analysis was conducted simply to assess the likelihood of finding a significant effect of the intervention [15]. The post hoc power analysis suggested the study did have the power to detect a mediation effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study was not powered to test such an association a priori, as the power analysis was conducted simply to assess the likelihood of finding a significant effect of the intervention [15]. The post hoc power analysis suggested the study did have the power to detect a mediation effect.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the study are reported in two previous reports [15, 16]. Inclusion criteria to the study were: between 18 and 65 years old; met criteria for ASPD using the Mini International Neuropsychiatric Interview [24]; and able to provide written informed consent; seeking treatment or already in treatment for a SUD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations